Analysis of the drainage effect of different incisions for high complex anal fistula based on FLUENT hydrodynamic simulation - Zhang, Jiamin; Li, Xiang; Ma, Jiaze; Chen, Peng; Li, Wanli; Hu, Junjie; Li, Xiaoliu; Chen, Yile; Ding, Kang (Frontiers in Surgery, 2022)
Purpose The biomechanical characteristics of the trauma size and postoperative drainage of different incisions for high complex anal fistula surgery were compared by numerical simulation analysis to provide a theoretical basis for the clinical selection of minimally invasive incisions for surgery. Methods Using FLUENT finite element software, a typical incision finite element model was established to obtain incision areas, and the total mass outlet flow within 200 s was calculated to evaluate the drainage effect of each incision. Results The incisions with the largest to smallest areas were the curved, spindle, and curved plus extended groove incision, indicating that the curved plus extended groove incision caused the least damage to the perianal skin muscles. Conversely, the incisions with the largest to smallest total outlet flow were as follows: curved plus extended groove, spindle, curved, and straight incision, suggesting that the curved plus extended groove model had the best diversion effect, and the curved incision had better diversion effect than that of the straight incision. Conclusion The curved plus extended groove surgical incision had the smallest incision area, minimized damage to the perianal skin and muscle tissue, conformed to the concept of minimally invasive surgery, ensured adequate drainage of exudate, maintained the normal growth of granulation tissue on the wound surface, preserved the original form of the anus, and thus better protected the function of the anus. This improved the quality of life of patients requiring high complex anal fistulas.